2017
DOI: 10.1038/nrurol.2017.125
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics and clinical significance of histological variants of bladder cancer

Abstract: In the past 10 years evidence for the clinical relevance of variant histology in urinary bladder cancer has been increasing. This increase has resulted in new classifications of urothelial cancers by the WHO in 2016, highlighting the importance of an accurate morphological description of pathological specimens for the therapeutic management of patients with bladder cancer. The rising awareness of the importance of an accurate pathological report manifests itself in the increasing prevalence of reporting of var… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
116
1
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 156 publications
(123 citation statements)
references
References 149 publications
3
116
1
3
Order By: Relevance
“…Current literature provides increasingly valuable data on the clinical significance and therapy‐related issues concerning urothelial carcinoma with variant histology compared to conventional urothelial carcinoma. In general, variant urothelial carcinoma is considered an aggressive feature as it worsens overall survival due to a higher rate of upstaging after surgery . Gofrit et al .…”
Section: Variant Urothelial Carcinoma In Clinical Practicementioning
confidence: 99%
“…Current literature provides increasingly valuable data on the clinical significance and therapy‐related issues concerning urothelial carcinoma with variant histology compared to conventional urothelial carcinoma. In general, variant urothelial carcinoma is considered an aggressive feature as it worsens overall survival due to a higher rate of upstaging after surgery . Gofrit et al .…”
Section: Variant Urothelial Carcinoma In Clinical Practicementioning
confidence: 99%
“…However, the management of patients who have urothelial carcinoma with variant histology is complex and more challenging. Moreover, the impact of variant histology on outcomes of treatment vary for those with and without muscle‐invasive disease …”
Section: Introductionmentioning
confidence: 99%
“…For pure squamous cell carcinoma, there is a predilection for immediate surgical resection, because this histologic subtype generally is associated with a poor response to chemotherapy . For micropapillary differentiated urothelial carcinoma, there is no consensus regarding the optimal treatment . In 2014, a study investigating the effect of adjuvant chemotherapy (AC) revealed a higher tumor recurrence rate but a similar cancer‐specific survival rate compared with pure urothelial carcinoma …”
Section: Introductionmentioning
confidence: 99%
“…Sixth, the presence of histological variants and its effect on survival outcomes was not tested in this cohort as it was not available for the whole cohort. We recognize the importance of this parameter [25] and the potential bias introduced by excluding this parameter from the analyses. Seventh, no data regarding the presence of macroscopic residual disease after surgery was included in the database.…”
Section: Discussionmentioning
confidence: 99%